PENGARUH METODE PROYEK TERHADAP TANGGUNG JAWAB PADA ANAK USIA 5-6 TAHUN DI TK RIZANI PUTRA MUARO JAMBI - Marsella Herliana Putri; Nyimas Muazzomi; Winda Sherly Utami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of responsibility as a character trait in early childhood is a crucial aspect of personality and social attitude formation. However, in practice, children’s responsibility has not yet developed optimally due to learning activities that tend to be teacher-centered and provide limited opportunities for active involvement. This study aimed to examine the effect of the project method on the responsibility of children aged 5–6 years at TK Rizani Putra. The study employed a quantitative approach using an experimental method with a one-group pretest–posttest design. The research subjects consisted of 17 children from group B. Data were collected using an observation instrument measuring children’s responsibility based on early childhood social-emotional development indicators. Data analysis was conducted using descriptive statistics, a normality test with the Shapiro–Wilk test, and hypothesis testing using a paired sample t-test. The results showed that the mean responsibility score increased from 17.25 in the pretest to 24.82 in the posttest. The normality test indicated that the data were normally distributed, meeting the assumptions for parametric analysis. Furthermore, the results of the paired sample t-test revealed a significant difference between children’s responsibility scores before and after the implementation of the project method. These findings indicate that the project method has a significant effect on improving responsibility in early childhood. Therefore, the project method can be considered an effective alternative learning strategy for developing responsibility character in early childhood education.